Hydro-Oceanographic and Water Quality Assesments As a Basis for the Development of Offshore Aquaculture in the Weh Island, Aceh Province, Indonesia - Koko Ondara; Try Altanto; Guntur Adhi Rahmawan; Ruzana Dhiauddin; Ulung Jantama Wisha; Nia Naelul Hasanah Ridwan (Aceh International Journal of Science and Technology, 2019)
The waters of Weh Island, Aceh Province has potency become the area for offshore aquaculture. Offshore Floating Net Cages can be an appropriate technology in increasing the biomass cultivation in Weh Island waters. However, no feasibility study has been done.  Therefore, this study aims to examine the suitability of offshore aquaculture locations in the East and South regions of Weh Island Based on Hydro-oceanography parameters. The parameters examined were water quality parameters such as temperature, brightness, pH, salinity and dissolved oxygen. In addition, we also examined the aspects of physical oceanography such as tides, currents and bathymetry. The results show that the water depth ranged from 0-57 m. The tidal type in the Weh Island waters is mixed tide prevailing semidiurnal with the tidal range of 1.9 m. The average of current speed ranged from 19.03-37.67 cm/s with the directions predominantly toward northwest and southeast.  It is concluded that the water quality data show that the eastern and southern parts of Weh Island are categorized as the feasible locations for offshore aquaculture.  Keywords: Sabang, Hydro-oceanography, Fisheries, Offshoreaquaculture, Floating net cages